IDO1/TDO dual inhibitor RY103 targets Kyn-AhR pathway and exhibits preclinical efficacy on pancreatic cancer - Liang, Heng; Li, Tianqi; Fang, Xin; Xing, Zikang; Zhang, Shengnan; Shi, Lei; Li, Weirui; Guo, Leilei; Kuang, Chunxiang; Liu, Hongrui; Yang, Qing (Cancer letters, 2021)
Indoleamine 2,3-dioxygenase 1 (IDO1) catalyzing the conversion of tryptophan (Trp) to kynurenine (Kyn) in kynurenine pathway (KP) is involved in the immunosuppression in pancreatic cancer (PC), but the value of IDO1 as an independent prognostic marker for PC is uncertain. Moreover, the correlation between tryptophan 2,3-dioxygenase (TDO), an isozyme of IDO1, and PC is largely unknown. Using TCGA database, the correlation between IDO1 and/or TDO expression and PC patients’ survival was analyzed. The expressions of IDO1 and TDO in PC cells and PC mice were examined. The effects of IDO1, TDO or dual inhibition on IDO1 and TDO effector pathway (Aryl hydrocarbon receptor, AhR) and on migration and invasion of PC cells were investigated. The block effect of IDO1/TDO dual inhibitor RY103 on KP was evaluated. The preclinical efficacy of RY103 and its immunomodulatory effect on KPIC orthotopic PC mice and Pan02 tumor-bearing mice were explored. Results showed that IDO1/TDO co-expression is an independent prognostic marker for PC. RY103 can significantly block KP and target Kyn-AhR pathway to blunt the migration and invasion of PC cells, exhibit preclinical efficacy and ameliorate IDO1/TDO-mediated immunosuppression in PC mice. •IDO1 and TDO generally exist in PC cells and mice, IDO1/TDO co-expression is an independent prognostic marker for PC.•IDO1/TDO dual inhibitor RY103 can significantly block KP without cytotoxicity.•RY103 targets the Kyn-AhR pathway to blunt the migration and invasion of PC cells in vitro.•RY103 exhibits greater preclinical efficacy than IDO1 selective inhibitor 1-L-MT in vivo.•RY103 ameliorates the immunosuppressive tumor microenvironment of KPIC orthotopic PC mice and Pan02 tumor-bearing mice.